ПРОЕКТ «ВСЕ ВМЕСТЕ СКАЖЕМ НЕТ ПЫТКАМ В МОЛДОВЕ: ГРАЖДАНСКОЕ ОБЩЕСТВО ПРОТИВ ПЫТОК»: ПРОВЕДЕНИЕ СЕМИНАРОВ СРЕДИ СОТРУДНИКОВ ПЕНИТЕНЦИАРНЫХ УЧРЕЖДЕНИЙ, ПОЛИЦИИ И ПСИХИАТРИЧЕСКИХ ЛЕЧЕБНИЦ РЕСПУБЛИКИ МОЛДОВА - Боршевский, Андрей Петрович; Сосна, Борис Ильич (SUPREMANCE OF LAW, 2019)
Torture violates fundamental human rights, therefore it is necessary to fight against it. The prohibition of torture is set out in many international acts, and also the legislation of the Republic of Moldova prohibits torture. However, despite this, torture is used in most countries around the world. This article provides a definition of torture, as well as recommendations for reducing torture. This article contains a description of the project “Let All of Us Say NO to Torture in Moldova: Civil Society against Torture”, project achievements. Th is article was prepared by the Institute for Democracy (Moldova). Th is article is funded by the European Union (European Instrument for Democracy and Human Rights). Opinions expressed in the article do not necessarily represent those of the European Union.
Keywords: UN; United Nations Convention against Torture; Moldova; torture; Institute for Democracy.